The assessment of population exposure to chlorination by-products: a study on the influence of the water distribution system - Levallois Patrick; Sérodes Jean; Rodriguez Manuel J; Legay Christelle (BMC, 2010)
Abstract Background The relationship between chlorination by-products (CBPs) in drinking water and human health outcomes has been investigated in many epidemiological studies. In these studies, population exposure assessment to CBPs in drinking water is generally based on available CBP data (e.g., from regulatory monitoring, sampling campaigns specific to study area). Since trihalomethanes (THMs) and haloacetic acids (HAAs) are the most documented CBP classes in drinking water, they are generally used as indicators of CBP exposure. Methods In this paper, different approaches to spatially assign available THM and HAA concentrations in drinking water for population exposure assessment purposes are investigated. Six approaches integrating different considerations for spatial variability of CBP occurrence within different distribution systems are compared. For this purpose, a robust CBP database (i.e., high number of sampling locations selected according to system characteristics) corresponding to nine distribution systems was generated. Results and conclusion The results demonstrate the high impact of the structure of the distribution system (e.g., presence of intermediary water infrastructures such as re-chlorination stations or reservoirs) and the spatial variability of CBPs in the assigned levels for exposure assessment. Recommendations for improving the exposure assessment to CBPs in epidemiological studies using available CBP data from water utilities are also presented.